Simulation of a Dummy Crash Test in Adams - Jaskiewicz, Marek; Frej, Damian; Poliak, Milos (Communications - Scientific Letters of the University of Zilina, 2022)
The article presents a model designed dummy for crash test in ADAMS. The simulated model dummy has dimensions, shapes and mass corresponding to a 50-percentile man. The simulation program allows modification of the dummy parameters. It allows to study the dynamics of motion, distribution of forces and loads of individual parts of the body of the simulated model. The article describes the design process and how to select the appropriate stiffness and damping joints for the simulated dummy. The article contains the results of simulation crash tests performed in the ADAMS program, which were compared to results of the Hybryd III dummy physical crash test. The simulation is designed to reflect the greatest compliance of the movements of individual parts of the human body during the low speed collision.
Keywords: computer simulation; dummy; crash test